PKM Pendampingan Literasi Digital dan Optimalisasi Digital Marketing sebagai Media Promosi Keripik Pisang - Cahyuni Novia; Siti Aida; Dewi Aminatus Zahro; Alfiatul Lailiyah (Universitas Nurul Jadid, 2023)
Many SMEs in Indonesia still experience difficulties in utilizing digital technology optimally. This was also experienced by Ibu Nur's Banana Chips UKM. So far, Ibu Nur's Banana Chips UKM has never carried out promotions using digital media because the owner does not know about digital technology that can be used as a digital marketing tool, so sales of Ibu Nur's Banana Chips often decline. This community service aims to provide counseling, training and assistance regarding what digital media can be used to promote Ibu Nur's Banana Chips SME products and to find out how to effectively promote products on various social media to support increasing sales of Banana Chips products. The method used in this service activity is lectures and training on the use of social media applications as a means of promoting Ibu Nur's Banana Chips products. The solution to this activity is to carry out digital literacy in Ibu Nur's Banana Chips UKM to increase knowledge about digital technology and optimize digital marketing using Google Maps and social media (Instagram, Facebook and WhatsApp business) as promotional tools. As a result of this service, SME owners can understand digital technology and optimize the use of social media platforms as a promotional tool there by increasing product sales.